Cue-based feeding in the NICU-a pathway to earlier oral feeding of preterm infants - Noa Ofek Shlomai; Chen Mordechai; Chen Mordechai; Iris Morag; Iris Morag; Tali Bdolach Abram; Smadar Eventov Friedman (Frontiers Media S.A., 2024)
AimTo compare volume-driven and cue-based feeding of low birth weight preterm infants, regarding short-term outcomes, including transition to oral feeds, weight gain, and length of stay.MethodsThis was a retrospective cohort study. Feeding and weight gain outcomes were compared between infants fed by volume-driven and cue-based feeds. The groups were subdivided by birth weight categories.ResultsThe study group included 240 low birth weight preterm infants born before 34 weeks of gestation, 120 infants fed by volume-driven feeding were compared to 120 infants fed by cue-based feeding. The groups were sub-analyzed by birth weight categories: <1,500 g and 1,500-2,500 g. Study groups were comparable regarding baseline characteristics and neonatal morbidities. Infants fed by cue-based feeding were more likely to achieve full oral feeding faster and at an earlier gestational age. Infants with a birth weight <1,500 g were less likely to experience adverse respiratory episodes during cue-based feeding. Although the rate of weight gain was reduced in cue-based feeding in the heavier infant group, discharge weight, breastfeeding rates, and length of stay were comparable between the groups.ConclusionsCue-based feeding results in faster transition to full oral feeding in very low birth weight preterm infants and at an earlier gestational age.